Quadruple Helix Approach to Boost Fashion Industry Innovation - Hermawan, Iwan; Sartono, Sartono; Hindrawati, Gita; Suharmanto, Suharmanto; Adah, Nur Nelisa (Inclusive Society and Sustainability Studies, 2024)
Currently, the fashion industry continues to grow and increase, but there is a problem gap in the form of declining demand for orders and stagnant fashion products, which has an impact on 3,000 textile factory workers in Sukoharjo Regency who have been laid off. The problem gap needs to be resolved through the collaborative roles of the sectors in the quadruple helix consisting of the fashion industry, universities, government, and civil society. Therefore, the research question is how does the fashion industry build innovation through the support of sectors in the quadruple helix? The purpose of this study is to identify the role of the quadruple helix in encouraging the fashion industry to create innovations that have an impact on employment. The research method used was a qualitative study with the informants being the Industry Office as the government sector, two fashion MSMEs as industry sector representatives, one university in Indonesia as the university sector, and a sample from civil society. The results of this research indicate that the industry sector is the primary driver of innovation, universities provide foundational knowledge for other sectors, and the government plays a role in maintaining the smooth operation of the fashion industry through policies. Additionally, civil society is responsible for evaluating the work of industry, universities, and government policies. This research contributes to the body of knowledge on the quadruple helix innovation theory.